Occurrence of ventricular and supraventricular arrhythmias according to the clinical profile of chronic renal patients undergoing hemodialysis: study at the Real Hospital Português de Pernambuco (Research, Society and Development, 2021)
Introduction: In recent years, Chronic Kidney Disease has been considered a serious public health problem. This is mainly due to the high annual mortality, due to cardiovascular disorders. Some of the main factors responsible for the mortality of this population are arrhythmic events. Given this perspective, the present study aimed to investigate the prevalence of ventricular and supraventricular arrhythmias in patients with dialysis chronic kidney disease. This is a prospective cohort study, in which the presence of cardiac arrhythmias and risk of sudden cardiac death was evaluated in 35 patients at Real Hospital Português de Pernambuco. Results: It was observed that 71.4% of the patients are male, 85.7% are not black and 57.1% are over 50 years old. Patients with inadequate plasma levels of potassium, calcium and those who did not use medications, had a higher prevalence of ventricular and supraventricular arrhythmias. Discussion: Changes in normal levels of calcium and potassium generate cardiovascular complications, especially arrhythmias. Higher prevalence of arrhythmias in individuals without medication use may be related to the fact that many patients are underdiagnosed. In addition, there was a higher prevalence of ventricular arrhythmia during hemodialysis when compared to supraventricular arrhythmia. Age proved to be an important factor related to arrhythmias in dialysis patients. Conclusion: Chronic renal patients on dialysis are found to have alterations in normal electrolyte levels and arterial hypertension that increase the occurrence of cardiac arrhythmias, especially ventricular, increasing the risk of sudden death in this population.